DNA Barcoding on Indian Ocean Squid, Uroteuthis duvaucelii (D'Orbigny, 1835) (Cephalopoda: Loliginidae) from the Java Sea, Indonesia - Norma Afiati; Subagiyo Subagiyo; Christina Retna Handayani; Retno Hartati; Nenik Kholilah (Faculty of Fisheries and Marine Universitas Airlangga, 2022)
Highlight ResearchThe possibility of U. duvauceli be a polymorph cryptic species is further reinforced by the results of the present study.Phylogenetic analysis showed two separate clusters though did not perfectly segregate north to the south waters.Individuals in cluster II from the south coast showed the highest polymorphism levels by 40 segregating sites (S), compared to only 2-4 sites in that of cluster IFrequencies of A, C, G, and T in mitochondrial DNA of all specimens skewed toward A and T, with T being the most preferred and G being the least preferred nucleotideAll specimens showed no amino acid frequency for glutamic acid. Further, all four individuals in cluster II (south coast) were also have no amino acid frequencies for aspartic acid and valine as well.AbstractUroteuthis duvauceli (D' Orbigny, 1835) also known as the Indian Ocean Squid is a highly important commercial marine organism along the Java coast, Indonesia. Based on genetic variation this species-complex are polymorphic and cryptic. In the present study, the genetic diversity and stock structure of loliginid squid U. duvauceli is investigated using a mitochondrial gene cytochrome oxidase subunit I (COI). Samples were collected by hand-jigging onboard of an 8hp small fisher-boat equipped with a few lamps during May to August 2015, May 2016 and August to November 2018. Sample collection started at dusk until midnight. The attractor was a weighed-quill attached to nylon string, manually immersed into the water and pulled quickly and continuously for about 3-5 minutes at each effort. The determination was conducted with BLAST. Phylogenetic analysis showed two separate clusters with 100% bootstrap value, in which cluster II from Palabuhanratu has divergences of 5.9 - 7.0%, compared to cluster I. Genetic variations exist within and among individuals over the locations. Palabuhanratu individuals have the highest polymorphism levels compared to other locations as shown by 40 segregating sites (S). Frequencies of A, C, G, and T in mtDNA of the 20 specimens U. duvauceli are biased toward A and T, with T being the most favoured and G being the least favoured nucleotide. All specimen showed no amino acid frequency for glutamic acid and all four individuals in cluster II (south coast) also have no amino acid frequencies for aspartic acid and valine as well.